Impact of a Chest Support on Lower Back Muscles Activity During Forward Bending - Armaĝan Albayrak; Richard H. M. Goossens; Chris J. Snijders; Huib de Ridder; Geert Kazemier (Applied Bionics and Biomechanics)
The present study is based on previous research on the poor body posture of surgeons and their experienced discomfort during surgical procedures. Since surgeons have head-bent and back-bent posture during open surgical procedures, a chest support is a viable supporting principle. This support is meant to reduce lower back pain by minimising lower back muscle activity. The aim of this study is to investigate the impact of a chest support on lower back muscle activity during forward bending and to establish a possible relation between supporting force and the kind of balancing strategy a person adopts. Use of the chest support shows a significant reduction of muscle activity in the lower back and leg muscles. Within the participants three user groups are identified as “sceptical users”, “non-trusters” and “fully trusters”, each following a different balancing strategy. Since there are different kinds of users, the designed body support should offer the possibility for altering the posture and should not constrain the user to take a certain body posture.